Law and economics analysis of housing policy - Kamiński, Maciej (Analiza prawna i ekonomiczna polityki mieszkaniowej, 2020)
The main aim of this paper is to verify the possibility of law and economics analysis in the field of housing policy. The object of the research is a housing policy model defined as the entirety of the legal acts regulating the actions of the state in reference to housing policy. The research is based on the new institutional economy, and law and economics analysis method. The theoretical part provides an overview of the main definitions of law & economics (LE), e.g. institution, contracts, transactions, property rights theory, transactions costs, with reference to the housing policy issues. Additionally, the criterions for efficiency ratings are presented (Pareto, Kaldor-Hicks, Caose claim, Posner) and the author’s proposal of defining housing policy is given. The empirical part is a comparative analysis of selected social housing policy programmes from the USA (LIHTC), the Netherlands (woningcorporaties) and Poland (TBS) at the viewpoint of the efficiency criteria
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 76-88
Keywords: housing policy; law and economics; New Institutional Economy; housing policy model; polityka mieszkaniowa; prawo i ekonomia; nowa ekonomia instytucjonalna; mieszkalnictwo